AB1009 THE EFFICACY OF TOCILIZUMAB ON THE TREATMENT OF TAKAYASU ARTERITIS IN CHINESE CHILDREN. (2nd June 2020) - Wang, C.; Song, H.; Yu, Z.; Quan, M.
Abstract : Background: Takayasu arteritis (TA) is the most prevalent large-vessel vasculitis in children. Patients with TA have a high mobidity and mortality.It remains a therapeutic challenge because corticosteroids monotherapy can rarely cure TAK and the relapse rate is high during GC tapering. Objectives: The aim of this study is to investigate the efficacy and safety of tocilizumab (TCZ)in Chinese children with Takayasu arteritis(TAK). Methods: We retrospectively studied 6 TAK children treated with TCZ in our hospital from July 2017 to October 2018. The demographic and clinical data, laboratory examination results and vascular imaging data were collected. Results: Six pediatric patients with critical or refractory TAK treated with TCZ were analyzed, including 3 males and 3 females.The diagnosis age was ranging in age from 2 to 13 years(median age:7 years).Three patients were initially treated with TCZ and Mycophenolate Mofetil(MMF) as the first-line regimen without corticosteroid or with a quite rapid GC taper duration, two of which had lifte-threatening coronary arteries involved and heart failure.The other three paitients were swcithed to TCZ from conventional disease modifying anti-rheumatic drugs (DMARDs) or other biologics due to being refractory to them and recurrent relapses.Four patients were given TCZ at 4 weeks regular intervals for 10 to 22 months, while two patients withdrew TCZ because of disease deterioration and unbearable abdominal or chest pain after the second dose.After 6 months follow-up, four patients experienced significant clinical and biological improvement with angiographically progression in one patient. A corticosteroid-sparing effect is obvious. Drug-related side effects occur in 1 patients manifesting as a mild elevated liver fuction. Neither neutropenia nor infection was observed. Conclusion: Our study shows a clinical, biological, and radiological response in patients with refractory TAK treated with TCZ. References: [1]Hellmich B, Agueda A, Monti S, et al.2018 Update of the EULAR recommendations for the management of large vessel vasculitis. Ann Rheum Dis 2019;0:1–12. doi:10.1136/annrheumdis-2019-215672. [2]BravoMancheño B, Perin F, Guez Vázquez Del ReyMDMR, García Sánchez A, Alcázar Romero PP. Successful tocilizumab treatment in a child with refractory Takayasu arteritis.Pediatrics 2012;130(6):e1720-724. [3]Goel R, Danda D, Kumar S, Joseph G. Rapid control of disease activity by tocilizumab in 10 «difficult-to-treat» cases of Takayasu arteritis. Int J Rheum Dis 2013;16(6):754–61. [4]Cañas CA, Cañas F, Izquierdo JH, Echeverri A-F, Mejía M, Bonilla-Abadía F, et al. Efficacy and safety of anti-interleukin 6 receptor monoclonal antibody (tocilizumab) in Colombian patients with Takayasu arteritis. J Clin Rheumatol Pract Rep Rheum Musculoskelet Dis 2014;20(3):125–9. [5]Batu ED, Sönmez HE, Hazirolan T, Özaltin F, Bilginer Y, Özen S. Tocilizumab treatment in childhood Takayasu arteritis: case series of four patients and systematic review of the literature. Semin Arthritis Rheum 2017 Feb;46(4):529–35. Disclosure of Interests: None declared